Pemikiran Ekonomi Syeikh Daud al-Fatani Menerusi Kitabnya Furu? al-Masa?il Tumpuan Kepada Elemen FiqhiConomic - Towpek, Hadenan; Borhan, Joni Tamkin (Jurnal Fiqh, 2012)
This article attempts to understand the concept of Islamic economic thought according to Syeikh Daud al-Fatani with special attention to the elements of FiqhiConomic. The initial review of this article applies the content analysis method to scrutinize the elements of FiqhiConomic, as discussed in his masterpiece Furu? al-Masa?il and specifically in reference to the chapter of muamalat (financial transactions). This article identifies the concept of Islamic economic thought as a process of ijtihad(reasoning) by Muslim scholars, based on the basic sources of Islamic law and other supporting sources, to find ways to address and solve the problems of muamalat and economics. In addition, the element of FiqhiConomic is formulated as an Islamic jurisprudence approach in addressing and resolving the problems of the economy. In this article, the conceptual understanding of FiqhiConomic elements are discussed according to three dimensions sanad continuity of scholarship tradition, FiqhiConomic dynamic approach, and several economic concepts related thereto. This article concludes that Malay scholars such as Syeikh Daud al-Fatani have a strong legacy and a progressive thinking that has the potential to expand more in various disciplines including Islamic economic thought.